Synthesis, Characterization, and Crystal Structures of New Oxovanadium(V) Complexes With Mixed Nicotinohydrazone and 8-Hydroxyquinoline Ligands. Issue 8 (2nd August 2016) - Sheng, Gui-Hua; Han, Xiao; Ye, Yu-Ting; Ren, Jin-Qi; You, Zhong-Lu; Zhu, Hai-Liang
Abstract : Two similar oxovanadium(V) complexes, [VOL 1 L′] (1 ) and [VOL 2 L′] (2 ), were prepared by the reaction of [VO(acac)2 ] (where acac = acetylacetonate), 8-hydroxyquinoline (HL′) with N′ -(5-fluoro-2-hydroxybenzylidene)nicotinohydrazide (H2 L 1 ) and N′ -(3-bromo-5-chloro-2-hydroxybenzylidene)nicotinohyrazide (H2 L 2 ), respectively, in methanol. Crystal and molecular structures of the complexes were determined by elemental analysis, infrared, and UV-vis spectra and single-crystal X-ray diffraction. The nicotinohydrazone ligands coordinate to the V atoms through the phenolate oxygen, imino nitrogen, and enolate oxygen. The 8-hydroxyquinoline ligand coordinates to the V atom through the phenolate oxygen and pyridine nitrogen. The V atoms in both complexes are in octahedral coordination.